Epistemic trust: a comprehensive review of empirical insights and implications for developmental psychopathology - Li, Elizabeth; Campbell, Chloe; Midgley, Nick; Luyten, Patrick (Research in psychotherapy (Milano)., 2023)
Originally rooted in philosophy and sociology, the concept of epistemic trust has recently transitioned to developmental psychopathology, illuminating social-cognitive processes in psychopathology. This narrative review synthesizes empirical evidence on epistemic trust to inform future research. A literature search highlighted 3 areas: i) the development of selective trust in children; ii) epistemic trust in non-clinical adults; iii) its link to mental health. Young children demonstrate selective learning from reliable sources using epistemic cues. Empirical studies beyond childhood were greatly facilitated in the last 2 years with the introduction of the Epistemic Trust, Mistrust and Credulity Questionnaire, a self-report scale measuring epistemic stance. Cross-sectional studies pinpointed dysfunctional epistemic strategies as factors in mental health vulnerability, and some qualitative work offered initial evidence linking restored epistemic trust to effective psychotherapy. For future research, we propose focusing on 3 primary areas. First, empirical investigations in adolescent samples are needed, as adolescence seems to be a pivotal phase in the development of epistemic trust. Second, more experimental research is required to assess dysfunctional and functional epistemic stances and how they relate to vulnerability to mental health disorders. Finally, intervention studies should explore the dynamics of epistemic stances within and between therapy sessions and their impact on therapeutic outcomes.